Comparative Study of a Modified Sub-Tenon’s Capsule Injection of Triamcinolone Acetonide and the Intravenous Infusion of Umbilical Cord Mesenchymal Stem Cells in Retinitis Pigmentosa Combined With Macular Edema - Zhao, Tongtao; Lie, Hongxuan; Wang, Fang; Liu, Yong; Meng, Xiaohong; Yin, Zhengqin; Li, Shiying (Frontiers in Pharmacology, 2021)
Retinitis pigmentosa (RP) is a hereditary retinal degenerative disease leading to eventual blindness. When RP is combined with macular edema (ME), the visual impairment further worsens. We compared a modified sub-Tenon’s capsule injection of triamcinolone acetonide (TA) and the intravenous infusion of umbilical cord mesenchymal stem cells (UCMSCs) in the treatment of RP combined with ME (RP-ME) to assess their safety and efficacy in eliminating ME and restoring visual function. A phase I/II clinical trial enrolled 20 patients was conducted. All patients were followed up for 6 months. There were no severe adverse effects in both groups. In retinal morphological tests, the central macular thickness (CMT) in TA group significantly decreased at 1st week, 1st and 2nd month after injection (P<0.05). The CMT in UCMSCs group significantly decreased at 1st month after infusion. The rate of reduction of CMT in TA group was significantly greater than that in UCMSCs group at 2nd month(P<0.05). Reversely, the rate of reduction of CMT in UCMSCs group was significantly greater than that in TA group at 6th month(P<0.05). In visual functional test, although there were no significant differences in visual acuity or visual fields within each group or between groups, but the amplitude of P2 wave of flash visual evoked potential (FVEP) showed significant increasing in TA group at 2nd month in UCMSCs group at 6th month (P<0.05). At 6th month, the rate of growth in the amplitude of P2 wave in USMCSs group was significantly greater than that in TA group (P<0.05). This study suggests both modified sub-Tenon’s capsule injection of TA and intravenous infusion of UCMSCs are safe for RP-ME patients. TA injection is more effective at alleviating ME while improving visual function in a short term. UCMSC intravenous infusion shows slow but persistent action in alleviating ME, and can improve the visual function for a longer time. These approaches can be applied separately or jointly depending on the disease condition for patients to benefit maximumly.